2012
DOI: 10.1111/j.1469-8137.2012.04206.x
|View full text |Cite
|
Sign up to set email alerts
|

A sensitive LC‐ESI‐Q‐TOF‐MS method reveals novel phytosiderophores and phytosiderophore–iron complexes in barley

Abstract: Summary The direct analysis of phytosiderophores (PSs) and their metal complexes in plants is critical to understanding the biological functions of different PSs. Here we report on a rapid and highly sensitive liquid chromatography‐electrospray ionization‐quadrupole‐time of flight‐mass spectrometry (LC‐ESI‐Q‐TOF‐MS) method for the direct and simultaneous determination of free PSs and their ferric complexes in plants. In addition to previously reported PSs – deoxymugineic acid (DMA), mugineic acid (MA) and epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 45 publications
1
42
0
Order By: Relevance
“…To confirm this, we examined NA secretion from barley (Hordeum vulgare) roots. In line with previously published reports (Howe et al, 1999;Suzuki et al, 2006;Tsednee et al, 2012), we found that NA was not detectable in barley root exudates, but was clearly detectable inside the root (Supplemental Fig. S1).…”
Section: Comparative Metabolite Profiling Of Root Exudatessupporting
confidence: 93%
See 4 more Smart Citations
“…To confirm this, we examined NA secretion from barley (Hordeum vulgare) roots. In line with previously published reports (Howe et al, 1999;Suzuki et al, 2006;Tsednee et al, 2012), we found that NA was not detectable in barley root exudates, but was clearly detectable inside the root (Supplemental Fig. S1).…”
Section: Comparative Metabolite Profiling Of Root Exudatessupporting
confidence: 93%
“…We did not detect the Fe(III)-NA complex. This might be because it has lower stability than Fe(II)-NA in the condition (von Wiren et al, 1999;Tsednee et al, 2012).…”
Section: Na Secreted From a Halleri Roots Forms A Stable Complex Witmentioning
confidence: 98%
See 3 more Smart Citations